Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2174/138161213804805775
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in the Pathogenesis and Prognosis of Esophageal Cancer

Abstract: Esophageal cancer (EC) is a deadly disease. EC usually occurs as either adenocarcinoma (EAC) or squamous cell carcinomas (ESCC). The development of EAC generally follows the metaplasia-dysplasia-carcinoma sequence. Barrett's esophagus (BE) is a metasplastic precursor of EAC. Multiple global miRNA expression profiling and candidate gene studies have been performed in EAC and ESCC that clearly support the important roles of miRNAs in the pathogenesis of EAC and ESCC. A number of consistently dysregulated miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 0 publications
2
61
0
Order By: Relevance
“…In the recent study, miR-203 has significantly low expression in cancer tissues compared to non-tumor counterparts (Viticchiè et al, 2011;Takeshita et al, 2012;Gu et al, 2013), while there were up-regulation of miR-203 was observed in pancreatic adenocarcinomas and breast, cancers (Naoki et al, 2010;Madhavan et al, 2012), we think the differential expression of miRNAs may be the result of tissue-specific differences. Just as Baffa et al suggested (Baffa et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…In the recent study, miR-203 has significantly low expression in cancer tissues compared to non-tumor counterparts (Viticchiè et al, 2011;Takeshita et al, 2012;Gu et al, 2013), while there were up-regulation of miR-203 was observed in pancreatic adenocarcinomas and breast, cancers (Naoki et al, 2010;Madhavan et al, 2012), we think the differential expression of miRNAs may be the result of tissue-specific differences. Just as Baffa et al suggested (Baffa et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies found that miR-192 is significantly increased in many types of cancer (39)(40)(41), but decreased in many others (42,43). Studies have also shown that p53-mediated upregulation of miR-192 prevents EMT in hepatocellular carcinoma through repression of the transcription factor ZEB2 (44).…”
Section: Discussionmentioning
confidence: 97%
“…In case of esophageal cancer, Wu et al (2011) and Kano et al (2010) reported that the expression levels of miR-143 and miR-145 was significantly decreased in many tissues of esophageal tissues in contrast to normal tissues [24,58]. However, Gu et al (2013) found no significant differences between the most examined miRNAs expression profiles including miR-93 and miR-143 in ESCC as well as in esophageal adenocarcinoma (EAC) [59]. In this study, no significant relationship was found between the expression of miR-93 and miR-143 and other clinicopathological features such as age or gender.…”
Section: Discussionmentioning
confidence: 99%